2005
DOI: 10.1111/j.1471-3802.2005.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of behaviour and patterns of exclusion: Gypsy Traveller students in English secondary schools

Abstract: This paper draws on a recent and unique longitudinal study of Gypsy Traveller students in fifteen local education authorities in England. Gypsy Traveller students are less likely to complete secondary education than any other minority ethnic group and it is estimated that up to 12 000 young Travellers in England are not registered at any secondary school. The study tracked a sample of 44 students over a three‐year period, using a multi‐perspective, phenomenological design to explore the complex interplay of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 4 publications
0
12
0
1
Order By: Relevance
“…Issues identified in the research in England, Scotland and Northern Ireland include: low educational participation/attendance, particularly at the secondary stages, low attainment, disproportionate disciplinary exclusion, racist harassment and bullying, a lack of continuity of work, interrupted learning, inconsistent/often inadequate support, problems with multiple registration, the failure of schools to pass on records/evidence of attainment; and children identified inappropriately with special educational needs (Lloyd & Stead, 2001a;Lloyd et al, 1999;Department for Education and Skills, 2003;Derrington & Kendall, 2003;Reynolds et al, 2003;Bhopal, 2004;Padfield & Jordan, 2004;Derrington, 2005;Scottish Parliament, 2005).…”
Section: Issues Of Marginalization and Educationmentioning
confidence: 99%
“…Issues identified in the research in England, Scotland and Northern Ireland include: low educational participation/attendance, particularly at the secondary stages, low attainment, disproportionate disciplinary exclusion, racist harassment and bullying, a lack of continuity of work, interrupted learning, inconsistent/often inadequate support, problems with multiple registration, the failure of schools to pass on records/evidence of attainment; and children identified inappropriately with special educational needs (Lloyd & Stead, 2001a;Lloyd et al, 1999;Department for Education and Skills, 2003;Derrington & Kendall, 2003;Reynolds et al, 2003;Bhopal, 2004;Padfield & Jordan, 2004;Derrington, 2005;Scottish Parliament, 2005).…”
Section: Issues Of Marginalization and Educationmentioning
confidence: 99%
“…This constitutes an important barrier for Roma children's education. Along these lines, Derrington (2005) found that parents' prior experiences in education and held beliefs about schools had an influence on breaking down home-school relationships as well as on Roma students' disengagement with secondary school. There is, therefore, a 'cultural dissonance' (Derrington, 2007) between the families' and the schools' expectations, which is a factor impacting Roma students' retention in education.…”
mentioning
confidence: 99%
“…Moreover, trust seems to be increased when the schools and school staff deals effectively with reported racism and bullying incidents (Bhopal 2011;Derrington 2007Derrington , 2005. The importance of commitment and dialogue of the school staff with members of the Roma community hence comes to the foreground Flecha and Soler 2013).…”
Section: Education In a Broader Societal Contextmentioning
confidence: 99%